2013
DOI: 10.1021/jp312844z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Gas-Phase Reactions of Sulfuric Acid Catalyzed Hydrolysis of Formaldehyde and Formaldehyde with Sulfuric Acid and H2SO4···H2O Complex

Abstract: The gas-phase reactions of sulfuric acid catalyzed hydrolysis of formaldehyde and formaldehyde with sulfuric acid and H2SO4···H2O complex are investigated employing the high-level quantum chemical calculations with M06-2X and CCSD(T) theoretical methods and the conventional transition state theory (CTST) with Eckart tunneling correction. The calculated results show that the energy barrier of hydrolysis of formaldehyde in gas phase is lowered to 6.09 kcal/mol from 38.04 kcal/mol, when the sulfuric acid is acted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
97
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 109 publications
16
97
0
Order By: Relevance
“…The similar mechanism in the initial step of the NH 2 + H 2 SO 4 reaction has also been found in the NH 2 + HNO 3 reaction . The pre‐reactive C2 A complex is formed via double hydrogen bondings, which is similar to sulfuric acid monohydrate complex …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The similar mechanism in the initial step of the NH 2 + H 2 SO 4 reaction has also been found in the NH 2 + HNO 3 reaction . The pre‐reactive C2 A complex is formed via double hydrogen bondings, which is similar to sulfuric acid monohydrate complex …”
Section: Resultssupporting
confidence: 87%
“…The O−H … N hydrogen‐bonded distance in C2 A is calculated to be 1.675 Å, while the O … H−N is estimated to be 2.485 Å in Figure S4 (Supporting Information), which is in good agreement with the corresponding values reported in the literature . In Table , C2 A has a binding energy of ‐10.88 kcal/mol with respect to the separate reactants H 2 SO 4 and NH 2 , which is close to the binding energy of ‐10.70 kcal/mol in the H 2 SO 4 … H 2 O complex at the CCSD(T)/aug‐cc‐pv(T+d)z//M06‐2X/6‐311++G(3df,3pd) level . It is worth noting that the binding energy between sulfuric acid and amidogen radical is stronger than that of the HNO 3 … NH 2 complex by about 2.5 kcal/mol.…”
Section: Resultssupporting
confidence: 79%
“…The M06-2X functional is one of the best functionals with which to study noncovalent interactions 38,39 and has shown promising applications for estimating the thermochemistry and equilibrium structures for atmospheric reactions and molecular clusters. [40][41][42] At the M06-2X/6-311++G(2d,2p) level, the harmonic vibrational frequencies were calculated to verify the nature of the corresponding stationary points (minima or transition state) to provide the zero-point vibrational energy (ZPE) and to determine the thermodynamic contributions to the enthalpy and free energy. In addition, intrinsic reaction coordinate (IRC) [43][44][45] calculations were carried out to ensure that the transition states were connected to the desired reactants and products.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…M06-2X functional has been widely used in theoretical calculation and can be better for ionic hydrogen-bonding interactions and identifying the global minimum conformer. [29][30][31][32][33][34][35][36] Been considered as the "gold standard" of quantum chemistry, CCSD(T) method was widely been used for reactions of organic matters and has high level accuracy. Thus we choose M06-2X functional at the 6-311++G(d,p) basis set for geometrical structures optimization and CCSD(T) method with the aug-cc-pVTZ basis set for single point energy calculation in this paper.…”
Section: Methodsmentioning
confidence: 99%